Seborrheic Keratosis Profile at Dr. Hasan Sadikin Central General Hospital Bandung 2015-2019 - Sutedja, Eva Krishna; Gradia, Resti; Latifah, Tri Aswila (UI Scholars Hub, 2022)
Background: Seborrheic keratosis (SK) is adults’ most prevalent benign skin tumor. SK originates from the proliferation of keratinocyte cells with varying morphology and degree of pigmentation. The lesions often resemble other types of malignancy. There are still many discrepancies in SK in Indonesia; hence, SK needs further understanding. This study aimed to describe the profile of seborrheic keratosis cases based on age, sex, location of lesions, and therapy at Dr. Hasan Sadikin Central General Hospital, Bandung, for five years Methods: This was a retrospective descriptive study with total sampling. Secondary data were collected from medical records of SK patients in the Tumor and Skin Surgery Polyclinic of Dr. Hasan Sadikin Central General Hospital, Bandung, from Jan 1, 2015, to Dec 31, 2019. A total of 105 medical records fulfilled the inclusion and exclusion criteria. Results: In most cases of SK, 41% occurred in middle-aged (40-59 years) patients. The average age was 49 ± 15 years old. Most patients, 64.8% were women. The location was mainly in the head and or neck (94.3%). SK was most frequently treated with a CO2 laser (56.2%), followed by electrocautery (36.2%). Conclusion: Most SK patients in this study were female, middle-aged (40-59 years), with lesions on the head and or neck, and were treated with CO2 laser.